Complete mitochondrial genome of the Endangered long-armed scarab Cheirotonus gestroi (Coleoptera: Euchiridae). Issue 1 (2nd January 2020) - Yang, Chen; Zhu, En-Jiao; He, Qiu-Ju; Yi, Chuan-Hui; Hu, Shao-Ji; Wang, Xu-Bo
Abstract: The long-armed scarab Cheirotonus gestroi is an endangered large insect in southwestern China and neighboring countries. Herein, we present the first complete mitochondrial genome of C. gestroi . The 16, 899 bp long circular genome consists of 2 ribosomal RNA genes, 22 transfer RNA genes, 13 protein-coding genes, and a non-coding control region. Phylogenetic analysis showed that C. gestroi shared the closest evolutionary relationship with C. jansoni and that Scarabaeidae and Lucanidae were correctly identified within superfamily Scarabaeoidea. The complete mitogenome sequence will provide a basis for further phylogenetic studies and conservation genetics of the genus Cheirotonus .